A dual‐system trusted computing node construction method based on ARM multi‐core CPU architecture. (21st April 2022) - Hong, Yu; Ning, Zhenhu; Sun, Yu; Shen, Changxiang
Summary: Computer node security is the source and foundation of information system security. Trusted computing dual system architecture is an important implementation method to solve the security assurance by establishing the dual system of computing nodes, on the one hand, to achieve isolation on the other hand to achieve the active metrics of the system. This article systematically analyzes the dual architecture of trusted computing, summarizes the security assurance implementation of the dual architecture of trusted computing as the problem of trusted platform control module (TPCM) trusted root parallel access bus, and designs and implements it using ARM multi‐core CPU architecture, and designs the basic hardware security assurance capabilities such as TPCM resource isolation, active metrics, secure communication and other key components of trusted cryptography module and trusted software base based on it, thus implementing the two core mechanisms of trustworthy computing, namely, trust chain construction and dynamic metrics, are implemented. The design of system integration in computing node devices based on this ARM multi‐core CPU architecture is proposed, and the related design and implementation methods are proposed, and finally, the prototype implementation and test verification are performed on the Phytium CPU platform.